Avaliação do impacto da inserção de geração fotovoltaica no fator de potência em sistemas de distribuição - Schmidt, Fernando Henrique Golke (2022)
With the growing interest of consumers of electric energy for the benefits brought by the Distributed Generation (DG), there is a concern about the impact that such insertion will bring to the distribution networks. After the changes brought to the sector by the Normative Resolution (REN) 687/15 of the National Electric Energy Agency (ANEEL), which led to the rapid growth of the sector in the country, there was a need for studies to mitigate the technical and commercial impacts that this type of generation brings to the electricity sector. One of the points impacted by the insertion of generation with the load is the power factor (PF). As DG's billing is focused on the active energy delivered to the network, the generating agent is not encouraged to control the generation PF, which is kept unitary in the generator, to produce only active energy. However, these consumers often also demand reactive energy, which necessarily needs to be provided by the grid, because, due to the lack of incentive, it is not generated by the DG units. As reactive energy is not billed to low voltage customers – only for the medium voltage, a technical and commercial problem arises, as this energy still causes losses and services to the concessionaire's network. Another point that can impact the PF of the grid, that is sometimes overlooked, is the level of harmonics entered by a consumer or generator. Thus, this work seeks to analyze the impact caused by the DG of a photovoltaic solar source on the PF of a distribution network with simulations through the OpenDSS software, through two case studies. The first case evaluates the consequences of the insertion of steps of active energy generation in the PF of the network, from the IEEE 37 bus system. Generation insertion steps are simulated with 10% power increments in relation to the installed load at each node, and the PF is analyzed at each simulation step. The second case evaluates the impact of harmonics insertion by photovoltaic inverters, through the implementation of a simple 225 kW three-phase load circuit and a 75 kW nominal power photovoltaic system, with measurements during the system's peak generation time. From this circuit, three different harmonics insertion scenarios are simulated, with low values found in commercial inverters, up to the limit values provided by regulations. From the analysis of the impact of the insertion of DG in the PF in the two case studies, it is concluded that the influence of this insertion cannot be disregarded, with the both analyzes being important.